Human rights groups in Malaysia: The case of the Suara Rakyat Malaysia (SUARAM) - Khoo, Y.H. (2014)
This paper is inspired by an interest to understand the roles and contributions of human rights advocacy groups to Malaysia and society. It aims to assess their effectiveness in advocating human rights, and the limitations that they face by referring the SUARAM as the case study. SUARAM has over the past two decades become one of the visible non-state actors in the country in its role to achieve better human rights protection. This study is concerned with how SUARAM has evolved, with special focus on its work in the area of civil and political rights. Despite changes in the political landscape of the country and the increase of civil actions and public awareness on the work of civil society groups, this paper argues that they can claim little achievements for the past years of human rights activism due to the rigid government policy, the non-human rights friendly legislation, and also its own internal organizational weaknesses. One significant aspect is the close link of human rights advocacy groups with the political parties that can lead to problems of credibility and transparency.